The Moral Paradox of Adverse Possession: Sovereignty and Revolution in Property Law - Katz, Larissa (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
On what grounds can we justify the transformation of squatters into owners? To understand the moral significance of adverse possession, the author proposes an analogy. Much of the moral analysis of adverse possession has proceeded on the basis that adverse possessors are land thieves. The author first explains why the analogy of adverse possessor to land thief is misleading. Then, she argues that there is a much closer analogy between adverse possession and revolution or, more precisely, a bloodless coup d’état. The recognition of the adverse possessor’s (private) authority solves the moral problem created by an agendaless object just as the recognition of the existing government’s (public) authority, whatever its origin, solves the moral problem of a stateless people. The morality of adverse possession, seen this way, does not turn on any particularized evaluation of the squatter’s deserts or her uses of the land. The author thus does not propose that adverse possession is justified in the same way that some argue a conscientious revolutionary is justified in resisting an oppressive or otherwise unjust sovereign. Rather, the morality of adverse possession is found where we might least expect it: in its positivist strategy of ratifying the claims to authority of a squatter without regard to the substantive merits of her agenda or her personal virtue.